Thiazole derivatives act on virulence factors of Cryptococcus spp - De Sa, Nívea Pereira; De Barros, Patrícia Pimentel; Junqueira, Juliana Campos; Vaz, Jéssica Aparecida; De Oliveira, Renata Barbosa; Rosa, Carlos Augusto; Santos, Daniel Assis; Johann, Susana (Oxford University Press (OUP), 2019)
Cryptococcosis is an opportunistic or primary fungal infection considered to be the most prevalent fatal fungal disease worldwide. Owing to the limited number of available drugs, it is necessary to search for novel antifungal compounds. In the present work, we assessed the antifungal efficacy of three thiazole derivatives (1, 2, and 3). We conducted in vitro and in vivo assays to investigate their effects on important virulence factors, such as capsule and biofilm formation. In addition, the phagocytosis index of murine macrophages exposed to compounds 1, 2, and 3 and the in vivo efficacy of 1, 2, and 3 in Galleria mellonella infected with Cryptococcus spp. were evaluated. All compounds exhibited antifungal activity against biofilms and demonstrated a reduction in biofilm metabolic activity by 43-50% for C. gattii and 26-42% for C. neoformans. Thiazole compounds promoted significant changes in the capsule thickness of C. gattii compared to that of C. neoformans. Further examination of these compounds suggests that they can improve the phagocytosis process of peritoneal murine macrophages in vitro, causing an increase in the phagocytosis rate. Survival percentage was examined in the invertebrate model Galleria mellonella larvae, and only compound 3 could increase the survival at doses of 5 mg/kg after infection with C. gattii (P= .0001) and C. neoformans (P= .0007), similar to fluconazole at 10 mg/kg. The results demonstrated that thiazole compounds, mainly compound 3, have potential to be used for future studies in the search for new therapeutics for cryptococcosis.
Keywords: Antifungal; Cryptococcus; Galleria mellonella; Thiazole; Virulence factor